Kualitas Laporan Keuangan pada Kantor Kementerian Agama Kabupaten Belu - Alycia Rika Fangidae; Anthon Simon Y. Kerihi; Herly M. Oematan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to determine the quality of financial reports at the Belu Regency Ministry of Religion office. This research uses a qualitative descriptive method. The data sources used in this research are primary data and secondary data. The research informants were the heads of the Belu Regency Ministry of Religion, planning and finance departments. The research was carried out in four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. based on research results regarding the quality of relevant financial reports, it is in accordance with Government Regulation No. 71 of 2010 which is the reference for determining quality financial reports. The results of research regarding the quality of reliable financial reports can be concluded that at the Belu Regency Ministry of Religion office it is not difficult to prepare financial reports because they are free from misleading meanings. The results of research regarding the quality of comparable financial reports can be concluded that the financial reports at the Belu Regency Ministry of Religion office provide information that can be compared with the previous period. The results of research regarding the quality of financial reports that can be understood can be concluded that financial reports are certainly not difficult for users to understand and will not hinder the decision-making process, for this reason the information in financial reports must be able to be understood by users, thereby making financial reports understandable because they can help the process. decision-making.